SECONDARY SPECIALIZED EDUCATION IN ENSURING THE POPULARIZATION OF SPORTS IN THE FIRST YEARS OF INDEPENDENCE (World Bulletin of Management and Law, 2023)
Independence of Uzbekistan, development of physical culture, sports rehabilitation in secondary specialized, vocational and technical educational institutions and ensuring the popularization of sports. The questions of training of educational institutions of personnel for the military direction in the system of secondary specialized education are analyzed.